Drug resistance mutations to integrase inhibitors, proteinase, and reverse transcriptase inhibitors in newly diagnosed HIV-1 infections in Hebei province, China, 2018–2022 - Lu, Xinli; Li, Yan; Liu, Meng; Wang, Yingying; An, Ning; Sun, Dandan; Li, Qi (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundHIV-1 protease (PR)-reverse transcriptase (RT) inhibitors as national free antiretroviral drugs have been used for 20 years. Integrase strand transfer inhibitors (INSTIs) have been conditionally used as a component of HIV/AIDS treatment regimens in recent years. However, the systematic investigation on the changes in primary drug resistance (PDR) in Hebei province, China was limited.MethodsA continuous cross-sectional investigation on HIV-1 PDR was conducted, integrating detection of drug resistance genotype, molecular network, and statistical analysis.ResultsThe overall prevalence of PDR was 8.3%, with 77 of 925 samples showing different levels of resistance to INSTIs (1.9%), protease inhibitors (PIs, 0.2%), nucleoside reverse transcriptase inhibitors (NRTIs, 1.2%), and non-NRTIs (NNRTIs, 5.2%). In the PR-RT gene coding region, E138EK/G was the most common (1.6%), followed by K103N (1.4%), G190GE/A/S (0.6%), K101E (0.5%), A98G (0.4%), and T215I/TS (0.3%), associated with the low- to high-level resistance to doravirine (DOR), efavirenz (EFV), etravirine (ETR), nevirapine (NVP), rilpivirine (RPV), and zidovudine (AZT). In the INSTI gene coding region, six mutations were identified, namely, four major mutations (P145PS, Q148QH, Y143S, and T66A) and two accessory mutations (S153SF and G163GRS/EK). Of these mutations, the most frequent INSTI mutations were S153SF (0.6%) and G163GRS/EK (0.6%), followed by P145PS (0.2%), Y143S (0.2%), Q148QH (0.1%), and T66A (0.1%). G163GRS/EK, P145PS, Y143S, and T66A were associated with the resistance to elvitegravir (EVG) and raltegravir (RAL). S153SF and Q148QH were mainly related to the resistance to dolutegravir (DTG), bictegravir (BIC), and caboteravir (CAB). Furthermore, 30 resistant sequences were circulating in 16 transmission networks with HIV-1 DR mutations (DRMs), accounting for 62.5% of 77 total participants with DRMs. Multivariable analysis showed that those who had CRF07_BC had 1.79 times greater odds of PDR compared with participants with CRF01_AE. Compared to participants with volunteer blood donor, those with voluntary consultation and testing had 0.27 times greater odds of PDR.ConclusionsThe overall prevalence of HIV-1 PDR in Hebei is high, belonging to a moderate resistant level (5.0%–15.0%). It is necessary for us to strengthen the effective surveillance of PDR among treatment-naive patients, and we should adjust the treatment plan according to the results of PDR surveillance.